A Foresight Study on Adoption of Blockchain Technology among Logistics Industry - Lim, Wei Jun; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2023)
Blockchain technology is relatively new in Malaysia. Although it has a significant potential influencing organizational strategies for implementation in respective operations, it has not yet been thoroughly investigated. Utilizing blockchain technology can enhance the performance of logistics, including concerns of traceability and transparency. However, there are concerns exist, regarding the lack of knowledge and limited past research on adoption blockchain technology in Malaysia. Consequently, the purpose of this study was to explore the issues and challenges on adoption of blockchain technology in the logistics business and to investigate the future of blockchain technology in Malaysia. In this study, both qualitative and quantitative methods was used. STEEPV analysis utilized as a foresight methodology. A survey questionnaire was used to identify the primary issues and drivers, as well as the impact-uncertainty analysis that corresponds to the adoption of blockchain technology. The respondents involved employees in the transportation and warehousing industry in Johor with a total of 117 respondents responded to the questionnaire. After achieving success in the development of impact uncertainty analysis, the third objective of scenario building based on impact uncertainty analysis is to pick the top two highest impact and uncertainty drivers for scenario building. Protecting data manipulation and societal resistance had the greatest effect on uncertainty, according to the findings of this study. This research has important implications for the implementation of Blockchain Technology in the logistics industry by future scholars and organizations.